Antidiabetic Activity and Chemical Composition of Sanbai Melon Seed Oil. (2nd May 2018) - Wang, Fang; Li, Haili; Zhao, Hang; Zhang, Ya; Qiu, Pengcheng; Li, Jie; Wang, Siwang
Abstract : Objectives. Many fruits and herbs had been used in Traditional Chinese Medicines for treating diabetes mellitus (DM); however, scientific and accurate evidences regarding their efficacy and possible mechanisms were largely unknown. Sanbai melon seed oil (SMSO) was used in folk medicine in treating DM, but there is no literature about these effects. The present study was aimed at confirming the treatment effects of SMSO in type 1 DM. Methods. Diabetes was induced by single intraperitoneal injection of streptozotocin (STZ) at a dose of 65 mg/kg body weight. After diabetes induction, mice were treated with SMSO at dose of 1 g/kg, 2 g/kg, and 4 g/kg. Drugs were given by gavage administration once a day continuously for 28 days. At the end of treatment, several biochemical parameters and molecular mechanisms were determined by biochemical assays, ELISA, and Western blotting. The chemical compositions of SMSO were also tested. Results. SMSO treatment significantly improved the symptoms of weight loss, polydipsia, reduced FBG level, increased plasma insulin levels, reduced plasma lipids levels, and protected islet injury. The results also showed that SMSO mitigated oxidative stress and alleviated the liver and renal injury in diabetes mice. SMSO also protected islet cells from apoptotic damage by suppressing ER mediated and mitochondrial dependent apoptotic pathways. Further constituent analysis results showed that SMSO had rich natural resources which had beneficial effects on DM. Conclusions. This study showed that SMSO had excellent antidiabetes effect and provided scientific basis for the use of SMSO as the functional ingredients production and dietary supplements production in the food and pharmaceutical industries.